Combined prevention of liver graft infection with hepatitis B virus - O. I. Andreitseva; S. V. Zhuravel; A. A. Salienko; A. V. Kozlova (Трансплантология (Москва))
The paper describes a case of successful cadaveric orthotopic liver transplantation (OLT) in a patient with hepatic B virus (HBV)-induced liver cirrhosis. It considers preoperative antiviral therapy with nucleoside analogues, including the occurrence of limivudine-resistant mutation in HBV (YMDD mutations) during long-term Zeffix therapy, the necessity of converting to entecavir (Baraclude). A combined immunoprophylaxis scheme using specific immunoglobulin (HB Ig, Neohepatex) and entecavir (Baraclude) is given for liver graft infection with HBV. The result of treating the patient was that the liver graft was not infected with HBV within 420 days after OLT.